2009
DOI: 10.1186/1471-2105-10-s12-s8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functionally related genes using data mining and data integration: a breast cancer case study

Abstract: Background: The identification of the organisation and dynamics of molecular pathways is crucial for the understanding of cell function. In order to reconstruct the molecular pathways in which a gene of interest is involved in regulating a cell, it is important to identify the set of genes to which it interacts with to determine cell function. In this context, the mining and the integration of a large amount of publicly available data, regarding the transcriptome and the proteome states of a cell, are a useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…proliferation, migration and differentiation into hypertrophic columnar cells, as well as apoptosis, apparently regulating the choice between the different fates a cell can have. As Gli3 remains expressed in the adult mammary gland [19], it may then perhaps likewise regulate the balance between normal homeostasis and tumor growth, as supported by the recent identification of Gli3 in a primary breast tumor expression dataset [41], and similar to what has recently been reviewed for several other genes [42], [43]. Of note, despite the similarities among MRs regarding the cellular mechanisms regulating their early growth, the function of Gli3 in these mechanisms differs among the MRs, indicating MRs are not mere copies of the same structure but distinct entities, as we have suggested previously [2].…”
Section: Discussionmentioning
confidence: 93%
“…proliferation, migration and differentiation into hypertrophic columnar cells, as well as apoptosis, apparently regulating the choice between the different fates a cell can have. As Gli3 remains expressed in the adult mammary gland [19], it may then perhaps likewise regulate the balance between normal homeostasis and tumor growth, as supported by the recent identification of Gli3 in a primary breast tumor expression dataset [41], and similar to what has recently been reviewed for several other genes [42], [43]. Of note, despite the similarities among MRs regarding the cellular mechanisms regulating their early growth, the function of Gli3 in these mechanisms differs among the MRs, indicating MRs are not mere copies of the same structure but distinct entities, as we have suggested previously [2].…”
Section: Discussionmentioning
confidence: 93%
“…In this respect MCL has been shown to perform as well or better than other network clustering algorithms [49]. Previous efforts to identify gene signatures/modules in cancer data have used different analytical approaches, less data, grouped far fewer genes and often failed to explain the biological significance of their findings [9-11,50,51]. Where correlation networks have been used previously to analyse modularity in gene expression data [13,52], available computing frameworks have not permitted the visualization or exploration of the resultant graphs as effectively in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…These findings together imply that Tbx3 cooperates with oncogenic Ras and c-Myc by suppressing ARF activity. A recent study identified GATA3 and GLI3 as putative TBX3 downstream targets in breast cancer (68). Although chromatin immunoprecipitation analysis confirmed direct binding of TBX3 to both of these targets, the functional significance of these findings is not known.…”
Section: Tbx3 In Cancermentioning
confidence: 99%